2013
DOI: 10.1073/pnas.1220543110
|View full text |Cite
|
Sign up to set email alerts
|

Pattern reorganization occurs independently of cell division during Drosophila wing disc regeneration in situ

Abstract: One of the most intriguing problems in developmental biology is how an organism can replace missing organs or portions of its body after injury. This capacity, known as regeneration, is conserved across different phyla. The imaginal discs of Drosophila melanogaster provide a particularly well-characterized model for analyzing regeneration. We have developed a unique method to study organ regeneration under physiological conditions using the imaginal discs of Drosophila. Using this method, we revisited differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 27 publications
(27 reference statements)
5
48
0
Order By: Relevance
“…In addition, the region of P3/4 samples is, indeed, overlaid with developmental wg expression; therefore, we assume that the expression of wound-induced wg would be masked in our microarray analysis. A recent study showed that the genes associated with pattern formation are temporally disrupted in damaged discs before initiating regenerative proliferation (40). In our data, cluster III comprised a significant number of developmental genes that are involved in the regional specification of leg disc development.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tosupporting
confidence: 56%
“…In addition, the region of P3/4 samples is, indeed, overlaid with developmental wg expression; therefore, we assume that the expression of wound-induced wg would be masked in our microarray analysis. A recent study showed that the genes associated with pattern formation are temporally disrupted in damaged discs before initiating regenerative proliferation (40). In our data, cluster III comprised a significant number of developmental genes that are involved in the regional specification of leg disc development.…”
Section: Upd Activates Jak/stat Signaling In Early Regenerating Discs Tosupporting
confidence: 56%
“…2E, F). 13 These results are consistent with findings using tissue ablation and irradiation to induce damage. 4,47 This de-specification did not require Wg signaling or regenerative proliferation.…”
Section: Discussion Of Findings and Relevant Literaturesupporting
confidence: 90%
“…2 While this method most closely approximates a traumatic wound or amputation, removing the tissue from the animal and subsequently culturing it likely induces additional stress responses. More recently, wounds in the tissue have been induced by pinching through the intact larval cuticle to make a cut 4,11,12 or remove a fragment 13 while leaving the wounded disc in place to heal and regenerate (Fig. 2B).…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations